An alternative thermal approach to evaluate the wettability of solder alloys. (25th August 2016) - Santos, Washington L.R.; Silva, Bismarck L.; Bertelli, Felipe; Spinelli, José E.; Cheung, Noé; Garcia, Amauri
Graphical abstract: Highlights: A thermal approach is proposed to qualitatively evaluate the wettability of solders. The approach is based on experimental results of solder/substrate thermal conductance. High temperature Zn-Sn solders are experimentally investigated. The approach is validated against experimental contact angles of wetting tests. The results indicate increase in wettability with decrease in alloy Sn content. Abstract: The aim of the work is to propose an alternative method to qualitatively evaluate the wettability of different alloys of a particular alloy system. The technique is based on a thermal approach supported by experimental/theoretical methodologies involving a directional solidification procedure and numerical simulations based on the solution of the inverse heat conduction problem (IHCP). The wettability strongly affects the heat ability to flow across the alloy/substrate interface during solidification, which is construed as a heat transfer coefficient (hg ). Particularly, for the alloys used in soldering processes, the wettability plays an important role in the integrity of solder junctions, being a fundamental parameter for selecting the most appropriate solder composition. The experiments were carried out with high temperature Zn-Sn solder alloys (10, 20, 30 and 40 wt%Sn) in a solidification device in which heat is extracted only through a water-cooled steel bottom. Experimental thermal profiles collected during solidification are used as input data to solve the IHCP and determine expressions hg vs. time for each alloy examined, permitting a tendency of wettability to be established. In order to validate the wetting behavior indicated by the hg values, alloy/substrate contact angles (θ) were measured on a steel substrate using a goniometer. It is shown that both hg and θ indicate improvements in wettability with the decrease in the alloy Sn content.